2017
DOI: 10.1111/fog.12247
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of larval Atlantic menhaden (Brevoortia tyrannus) and Atlantic croaker (Micropogonias undulatus): Implications for vertical migratory behaviour and transport

Abstract: Understanding the interactions among biological and physical processes is essential to determining how the environment affects transport and survival of fishes. We examined vertical distribution in larval Atlantic menhaden (Brevoortia tyrannus) and Atlantic croaker (Micropogonias undulatus) using 126 depth stratified tows in Delaware Bay, USA, during two cruises, in December 2007 and February 2008. Menhaden larvae were 16.8–24.6 and 20.5–26.2 mm standard length in December and February. Corresponding lengths f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…The chi-square (χ 2 ), degrees of freedom (df), and probability (P) values represent the results of a goodness-of-fit test to evaluate whether each size-class of fish showed an inherent preference or avoidance of compartments in the absence of a salinity gradient. (Hare et al 2005) and active (bottom-layer-oriented behavior and flood tide transport (sometimes referred to as selective tidal stream transport) processes (Weinstein et al 1980;Joyeux 1999;Reiss and McConaugha 1999;Hare et al 2005;Schaffler et al 2009;Schieler et al 2014;Hale and Targett 2018). Furthermore, increased reliance on active behavioral responses has been reported to occur with ontogenetic development in young Atlantic Croakers (Hare et al 2005;Hale and Targett 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chi-square (χ 2 ), degrees of freedom (df), and probability (P) values represent the results of a goodness-of-fit test to evaluate whether each size-class of fish showed an inherent preference or avoidance of compartments in the absence of a salinity gradient. (Hare et al 2005) and active (bottom-layer-oriented behavior and flood tide transport (sometimes referred to as selective tidal stream transport) processes (Weinstein et al 1980;Joyeux 1999;Reiss and McConaugha 1999;Hare et al 2005;Schaffler et al 2009;Schieler et al 2014;Hale and Targett 2018). Furthermore, increased reliance on active behavioral responses has been reported to occur with ontogenetic development in young Atlantic Croakers (Hare et al 2005;Hale and Targett 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(Hare et al 2005) and active (bottom-layer-oriented behavior and flood tide transport (sometimes referred to as selective tidal stream transport) processes (Weinstein et al 1980;Joyeux 1999;Reiss and McConaugha 1999;Hare et al 2005;Schaffler et al 2009;Schieler et al 2014;Hale and Targett 2018). Furthermore, increased reliance on active behavioral responses has been reported to occur with ontogenetic development in young Atlantic Croakers (Hare et al 2005;Hale and Targett 2018). Our finding that 26-40-mm fish showed strong behavioral preferences for high salinities in the laboratory supports that active selection behaviors continue ontogenetically and assist the up-estuary transport of early juveniles in this size range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful recruitment of young-of-the-year (age-0) fishes has been linked to environmental processes (e.g., Boehlert and Mundy 1988;Hare and Govoni 2005;Lehodey et al 2006;Cury et al 2008). Previous studies have shown that nekton size (Hale and Targett 2018), temperature (Witting et al 1999;Lankford and Targett 2001;Hare and Able 2007;Carassou et al 2011;Yasumiishi et al 2016), salinity (Lankford and Targett 1994;Able et al 2009), freshwater input (Reist et al 2006;Carassou et al 2011), flow (Dunning et al 2009), and wind speed and direction (Nye et al 2014;Schieler et al 2014) can significantly affect transport, growth, and survival of multiple life stages of marine nekton. The NAO and AMO have been linked to trends in fisheries production, distribution, and abundance (Lehodey et al 2006).…”
mentioning
confidence: 99%